2018
DOI: 10.22215/cjcr.v5i1.1241
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Children and Youth Participation into Resilience Planning

Abstract: Article 12 of the United Nations Convention on the Rights of the Child of 1989 places obligations on States to provide opportunities for children to express their opinions and to have these opinions be taken seriously in matters that affect their lives. While many studies from around the world have shown that children and youth can meaningfully participate to inform a wide range of issues, wide-scale implementation of children’s participation and thus the realization of children’s rights, is still not widely a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In responding to these challenges, many child studies nevertheless confirm the capacity and capability of young citizens to accurately perceive urban spaces and their competency in having a voice contributing to place-making (Carroll et al, 2019;Cele & Van der Burgt, 2015;Derr et al, 2018;Hanssen, 2019;Reiersølmoen et al, 2017). Some scholars, however, emphasise the process as a joint collaboration between children and other influential actors.…”
Section: Integration Of Children Into Urban Planning Agendamentioning
confidence: 99%
“…In responding to these challenges, many child studies nevertheless confirm the capacity and capability of young citizens to accurately perceive urban spaces and their competency in having a voice contributing to place-making (Carroll et al, 2019;Cele & Van der Burgt, 2015;Derr et al, 2018;Hanssen, 2019;Reiersølmoen et al, 2017). Some scholars, however, emphasise the process as a joint collaboration between children and other influential actors.…”
Section: Integration Of Children Into Urban Planning Agendamentioning
confidence: 99%
“…As a result, there has been a notable increase in youth participation in public policy in recent years. A study on resilience-oriented urban planning in Mexico City, Boulder (US), and Thessaloniki (Greece) showed that the youth can significantly contribute to urban planning by identifying ways in which infrastructures can be built to support vulnerable social groups such as the homeless and themselves [18]. A study of the Growing Up in Cities (GUIC) program of UNESCO and the Child Friendly Cities Initiatives (CFCI) of UNICEF also made similar observations in Denver (USA) [19].…”
mentioning
confidence: 99%